“Good childhood”: children’s perception and evaluation of transnational families - König, Alexandra; Schwittek, Jessica; Jendrzey, Katarzyna (Frontiers in Sociology, 2024)
In public debates, transnational families are portrayed as a deviation from the norm of “good childhood.” In Europe, this is emphasized by the term “Euro-orphans,” branding parents’ (especially mothers’) absence as a violation and scandalizing it. Children’s voices are rarely heard in public discourse, and although research is now turning its attention to the “stayer children,” they and their perspectives on transnational family life remain underrepresented, especially in Europe. In a German-Polish project, we investigate how children perceive and evaluate transnational family life based on 27 group discussions with 12-14-year-olds (with and without own transnational family experience) in Poland. The analysis shows that (1) the presence of parents is central to the normative pattern of a good childhood from children’s perspective, but (2) they use differentiated criteria when assessing (temporary) parental migration, i.e., they do not refer to “universal” needs of children. Additionally, (3) children request that they be informed about the migration-decision early on and involved in the organization of the time of separation to make it as acceptable as possible for them. Thereby, they offer interpretations of transnational families that contribute to erode the norm of good childhood. We see our paper as a sociologically and socio-politically relevant contribution to expanding the discussion on transnational families, both from the perspective of children who discuss and problematize transnational family life as more than merely a question of violating the norm of parents’ presence, and with our focus on the European region, which provides specific contextual conditions for transnational families.